Prediction of beef meat fatty acid composition by visible-near-infrared spectroscopy was improved by preliminary freeze-drying. (December 2019) - Andueza, D.; Listrat, A.; Durand, D.; Normand, J.; Mourot, B.P.; Gruffat, D.
Abstract: The aim of this study was to compare visible-near-infrared spectroscopy (VIS/NIRS) models developed from fresh or freeze-dried samples for predicting the fatty acid (FA) composition of beef samples. The hypothesis tested is that the removal of water from samples could improve the VIS/NIRS model performance. A total of 454 beef samples obtained from different bovine muscles were used. No significant differences were found in the performance of VIS/NIRS models developed from fresh or freeze-dried samples for predicting both major individual FAs and families of FAs and for some FAs (16:0, 18:0, 18:1 n -9, 18:2 n -6, 20:4 n -6, 22:5 n -3, 22:6 n -3, saturated, mono-unsaturated FA, and total n-3 long chain poly-unsaturated FAs (PUFA)). In contrast, the standard error of predictions for total PUFAs, total n-3 PUFAs, total conjugated linoleic acid, 20:5 n -3, and 18:3 n -3 were improved (by 21% on average; P < .05) in freeze-dried samples compared with fresh samples. Highlights: NIRS was used for predicting beef meat fatty acids. We compared the use of fresh and freeze-dried meat samples. No differences between processing type for NIRS prediction of major fatty acids. Polyunsaturated fatty acids were better predicted when freeze-dried samples were used.